2006
DOI: 10.1038/labinvest.3700426
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between PDGF and IGF-I receptors in rat liver myofibroblasts: implication for liver fibrogenesis

Abstract: Insulin-like growth factor I (IGF-I) and platelet-derived growth factor (PDGF) have been identified as significant mitogens for liver myofibroblasts (LMFs), one of the cell populations playing a role in liver fibrogenesis. In the present work, we aimed to elucidate a possible interaction between PDGF receptor (PDGFR) and IGF-I receptor (IGF-IR) signaling in LMFs. Among different rat liver cells, PDGFR a-and b-subunits were mainly expressed in hepatic stellate cells and LMFs, and were upregulated during their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
(57 reference statements)
3
18
0
4
Order By: Relevance
“…These findings extend and confirm data derived from earlier studies of clonal HSC lines, in which Shh antibodies increased cellular apoptosis and recombinant Shh stimulated growth [29]. The present study also demonstrates that proliferative actions of PDGF-BB, a major HSC mitogen [45,46], are mediated via the Hh pathway because three distinct approaches that abrogate Hh signaling each significantly inhibited PDGF-related increases in HSC incorporation of BrdU. Both agents that specifically antagonize Hh signaling by preventing activation of discrete Hh pathway signaling components (Anti-Shh antibodies prevent Shh from activating Ptc, and cyclopamine prevents Ptc from activating Smo) [60], exerted comparable effects on HSC DNA synthesis, reducing the stimulatory actions of PDGF-BB by about 50%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings extend and confirm data derived from earlier studies of clonal HSC lines, in which Shh antibodies increased cellular apoptosis and recombinant Shh stimulated growth [29]. The present study also demonstrates that proliferative actions of PDGF-BB, a major HSC mitogen [45,46], are mediated via the Hh pathway because three distinct approaches that abrogate Hh signaling each significantly inhibited PDGF-related increases in HSC incorporation of BrdU. Both agents that specifically antagonize Hh signaling by preventing activation of discrete Hh pathway signaling components (Anti-Shh antibodies prevent Shh from activating Ptc, and cyclopamine prevents Ptc from activating Smo) [60], exerted comparable effects on HSC DNA synthesis, reducing the stimulatory actions of PDGF-BB by about 50%.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, subsequent studies addressed the effect of AKT activation on HSC expression of Shh. As expected [32,45,46], PDGF-BB elicited rapid phosphorylation of AKT on Thr308 and Ser473, with peak AKT activation occurring within the initial hour after PDGF-BB addition (Fig 4A). The ensuing accumulation of Shh protein was inhibited by addition of either the PI3 kinase inhibitor, Ly294002, which inhibits PDGF-BB activation of AKT [45] (Fig 4B) or adenovirally-mediated delivery of dominant negative AKT (Ad5dnAkt) (Fig 4C).…”
Section: Pdgf-bb Induction Of Shh Involves Akt-dependent Mechanismssupporting
confidence: 79%
See 1 more Smart Citation
“…Recent studies have reported the mitogenic action of myofibroblast differentiation and proliferation by IGF-1 8,9 .…”
Section: Igf-1 Expression Is Modulated During Wound Healingmentioning
confidence: 99%
“…der aktiven nichtdestruierenden Endometrosen) und TGF-b1 (nur inaktiven Endometrosen (Raila 2000). Stromal synthetisierte profibrotische Wachstumsfaktoren und Zytokine, wie beispielsweise PDGF, TNF-a, CTGF u.a., die bei verschiedenen Gewebsfibrosen nachgewiesen wurden (Antoniades et al 1990, Kapanci et al 1995, Leask et al 2002, Novosyadlyy et al 2006 Zusammenfassend kann festgestellt werden, dass eine mit der Leber-und Lungenfibrose vergleichbare Schlüsselrolle der TGF-Wachstumsfaktoren in der Pathogenese der equinen Endometrose anhand der vorliegenden Ergebnisse dieser Arbeit nicht eindeutig belegt werden kann. Eine generell erhöhte epitheliale und/oder stromale TGF-Wachstumsfaktor-Expression im Sinne einer "überschießenden" Wundheilungsreaktion wurde in der equinen Endometrose nicht nachgewiesen.…”
Section: Diskussionunclassified